2009
DOI: 10.1097/ccm.0b013e31819c3c67
|View full text |Cite
|
Sign up to set email alerts
|

Development of endotoxin tolerance in humans in vivo

Abstract: Endotoxin tolerance developed during five consecutive LPS administrations as demonstrated by the attenuated release of proinflammatory cytokines on the fifth day and was associated with less leukocyte and endothelial activation. In contrast to animal and human in vitro data, the attenuated response was not limited to the proinflammatory response, as a similar reduction in the anti-inflammatory cytokines was observed, with the exception of TGF-beta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 50 publications
11
99
0
5
Order By: Relevance
“…Therefore, it could be possible that the absence of PMNs results in an inability to dampen proinflammatory cytokine production like IL-1, which results in fever. In human experimental endotoxemia, exposure to bacterial endotoxin (LPS) leads to hyporesponsiveness to a new endotoxin challenge (55). It has been described that reduced TNF-a production plays a major role in endotoxin tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be possible that the absence of PMNs results in an inability to dampen proinflammatory cytokine production like IL-1, which results in fever. In human experimental endotoxemia, exposure to bacterial endotoxin (LPS) leads to hyporesponsiveness to a new endotoxin challenge (55). It has been described that reduced TNF-a production plays a major role in endotoxin tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the expression of TGF-␤1 significantly increased in endotoxin-tolerized human peritoneal macrophages (33), mouse macrophages (34), mouse dendritic cells (35), and human blood from sepsis patients (36). TGF-␤1 is also a major immunosuppressive cytokine and plays a vital role in the development of endotoxin tolerance (34,37).…”
Section: Siglec-1 Expression Significantly Up-regulated During Lpsindmentioning
confidence: 99%
“…Leukocytes of septic patients are poorly responsive to pathogen-associated molecular patterns (PAMPs) compared with cells from healthy subjects, reminiscent of the phenomenon of endotoxin tolerance (18)(19)(20). This modified immune status may facilitate the occurrence of secondary infections (20,21).…”
mentioning
confidence: 99%